In vivo evaluation of A-56619 (difloxacin) and A-56620: new aryl-fluoroquinolones. - Fernandes, P B (1986)
A-56619 and A-56620 are two new aryl-fluoroquinolones which are as potent as or more potent than norfloxacin when administered orally and subcutaneously in mouse protection tests against Staphylococcus aureus, Streptococcus pyogenes, and Streptococcus pneumoniae. A-56619 and A-56620 were more potent than norfloxacin when administered orally against Escherichia coli, Proteus mirabilis, Serratia marcescens, and Pseudomonas aeruginosa. A-56620 was as potent or two- to threefold more potent than norfloxacin when administered subcutaneously against members of the family Enterobacteriaceae and Pseudomonas aeruginosa. Infection with Salmonella typhimurium was more effectively treated with A-56619 (50% effective dose [ED50], 1.4 mg/kg per day) than with norfloxacin (ED50, 62.8 mg/kg per day). E. coli or Pseudomonas pyelonephritis in mice was more effectively treated with A-56619 or A-56620 than with norfloxacin. After oral treatment, the ED50s of A-56619 and A-56620 were less than 12.5 mg/kg per day against E. coli and 62.9 and 38 mg/kg per day against P. aeruginosa pyelonephritis, respectively. Norfloxacin was ineffective at 200 mg/kg per day against E. coli or P. aeruginosa pyelonephritis. A-56619 and A-56620 were also more potent than norfloxacin in treatment of mixed bacterial pyelonephritis caused by E. coli and Streptococcus faecalis. A-56619 was at least 30 times more potent than norfloxacin and A-56620 was 4 to 11 times more potent than norfloxacin when administered against Klebsiella pneumonia in mice. A-56619 and A-56620 were at least 2 to 10 times more potent than norfloxacin against Staphylococcus aureus infections in immunosuppressed mice. A-56619 was equally potent in all in vivo tests when administered orally or subcutaneously, whereas A-56620 was similar to norfloxacin in being more potent when administered subcutaneously. The peak serum levels after subcutaneous and oral administration of A-56619 and A-56620 were higher than that of norfloxacin. The serum hal-lives of A-56619 and A-56620 after subcutaneous and oral administration were longer than the serum half-life of norfloxacin.